Genotoxicity analysis of a flame retardant, aluminum diethylphosphinate - Leoncio, T. O.L.; Fernandes, A. S.; Felzenszwalb, I.; Araujo-Lima, C. F.; Oliveira, D. P. [UNESP]; Dorta, D. J. [UNESP]; Sampaio, C. F.; Ferraz, E. R.A. [UNESP] (Elsevier, 2024)
Flame retardants, crucial for fire prevention, are used worldwide, but they are considered to be ‘emerging contaminants’ and may pose risks to human and environmental health. Aluminum diethyl phosphinate (ALPI) is a halogen-free flame retardant. To evaluate the toxicity of this compound, the following assays were performed: Salmonella/microsome mutagenicity assay; toxicity assays with two endpoints (mitochondrial dehydrogenase activity, plasma membrane integrity); micronucleus assay with human hepatoma cell line HepG2. ALPI was not mutagenic in Salmonella strains TA97, TA98, TA100, TA102, or TA104. ALPI was not cytotoxic at any concentration tested. The HepG2 micronucleus assay showed genotoxicity of ALPI at 200 µg/mL and no cytotoxicity (cytokinesis-block proliferation index, CBPI). Our data are relevant to the regulation of flame retardants.
Keywords: Emerging contaminants; In vitro assays; Toxicity